Edukasi Penggunaan Gadget Untuk Kesehatan Mata Pada Siswa/Siswi SMP Negeri 4 Meulaboh - Sry Rizki; Asmima Yanti (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
The use of gadgets among children and adolescents has increased along with technological developments; however, excessive use duration can negatively impact eye health, particularly triggering eye fatigue (asthenopia). This community service activity aimed to improve the knowledge and awareness of students at SMP Negeri 4 Meulaboh regarding healthy gadget use to prevent eye disorders. The method used was counseling through interactive lectures, question-and-answer sessions, and the use of audiovisual media. The activity was held on June 20, 2025, attended by 30 students. The material covered the definition and purpose of gadget use, influencing factors, the negative effects of excessive use, the concept of eye health, causes of eye fatigue, and prevention strategies. The results showed an increase in participants’ understanding, as evidenced by their active participation and ability to answer evaluation questions. This activity is expected to foster healthy gadget-use habits, thereby minimizing the risk of eye fatigue.